Low-on-state haze liquid crystal dimming film and preparation method thereof
Patent Information
- Application Number
- CN202610843739.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请的目的是提供一种低开态雾度液晶调光膜及其制备方法,解决现有技术中液晶调光膜在低温环境下开态雾度高、响应速度慢的问题,同时降低驱动电压并提高力学性能
[0024]本申请第一方面提供的低开态雾度液晶调光膜,通过在液晶相中引入主体液晶、第一改性液晶和第二改性液晶的三元复合体系,特别是采用二硫化钼对液晶分子进行表面修饰制备的第二改性液晶,实现了优异的光学性能。在电场作用下,液晶分子需要沿电场方向有序排列以实现开态透明,而开态雾度主要来源于液晶微滴与聚合物基体之间的界面缺陷、液晶分子取向不完全以及微滴尺寸分布不均一导致的光散射。本申请通过引入两种改性液晶,特别是二硫化钼改性的第二改性液晶,显著改善了液晶分子在低温环境下的运动能力,使调光膜在-30℃时开态雾度仍保持在较低水平。
Smart Images

Figure CN123010281A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dimming film technology, specifically relating to a low-open-state haze liquid crystal dimming film and its preparation method. Background Technology
[0002] Liquid crystal / polymer composite electro-optical dimming films are widely used in building windows, automotive sunroofs, and displays due to their unique electro-optical properties. Polymer dispersed liquid crystal (PDLC) and polymer stabilized liquid crystal (PSLC) are two common liquid crystal / polymer composite material systems. However, existing liquid crystal dimming films generally suffer from problems such as increased on-state haze and slower response speed at low temperatures, making it difficult to meet the requirements of low-temperature applications.
[0003] In existing technologies, the non-uniform size of liquid crystal droplets and numerous interface defects lead to increased light scattering, especially at low temperatures where the movement of liquid crystal molecules is restricted, resulting in a significant increase in open-state haze. Furthermore, traditional PDLC systems have a high polymer content, leading to higher driving voltages; while PSLC systems, although having lower driving voltages, suffer from poorer mechanical properties, making large-area processing difficult. Summary of the Invention
[0004] The purpose of this application is to provide a low-open-state haze liquid crystal dimming film and its preparation method, which solves the problems of high open-state haze and slow response speed of liquid crystal dimming films in the prior art under low-temperature environment, while reducing the driving voltage and improving mechanical properties.
[0005] In a first aspect, this application provides a low-open-state haze liquid crystal dimming film, comprising a liquid crystal phase and a polymer phase, wherein the liquid crystal phase comprises a host liquid crystal, a first modified liquid crystal, and a second modified liquid crystal, wherein the second modified liquid crystal is obtained by surface modification of liquid crystal molecules with molybdenum disulfide.
[0006] Optionally, the weight ratio of the liquid crystal phase to the polymer phase is (70~80):(20~30), and the weight ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal is (65~75):(8~15):(3~8).
[0007] Optionally, the method for preparing the second modified liquid crystal includes:
[0008] Molybdenum disulfide powder was added to hydrochloric acid solution and stirred at 50-80℃ for 1-4 hours for acid activation treatment. Then, it was centrifuged and washed to obtain activated molybdenum disulfide nanoparticles.
[0009] The activated molybdenum disulfide nanoparticles are dispersed in an organic solvent to form a dispersion.
[0010] Liquid crystal monomers and free radical initiators are added to the dispersion, and the mixture is reacted at 65-75°C for 4-8 hours under inert gas protection to obtain a reaction mixture; wherein, based on the total mass of solid components in the reaction mixture, the activated molybdenum disulfide nanoparticles account for 10-30 wt%, the liquid crystal monomer accounts for 68-88 wt%, and the free radical initiator accounts for 0.5-3 wt%.
[0011] The reaction mixture was centrifuged, washed, and vacuum dried at 50-70°C for 8-16 hours to obtain the second modified liquid crystal.
[0012] Optionally, the liquid crystal monomer is selected from at least one of 4-cyano-4'-pentylbiphenyl, 4-cyano-4'-heptylbiphenyl, and 4-methoxy-4'-cyanobiphenyl;
[0013] Optionally, the molybdenum disulfide nanoparticles have an average particle size of 50-200 nm.
[0014] Optionally, the mass-to-volume ratio of the molybdenum disulfide powder to the hydrochloric acid solution is 1.0 g : 15~25 mL, and the concentration of the hydrochloric acid solution is 0.8~1.2 mol / L.
[0015] Optionally, the polymer phase is formed by UV-induced phase separation and curing of polymerizable monomers and photoinitiators, wherein the UV curing conditions are: light intensity 5~15mW / cm². 2 The irradiation time is 30-120 seconds, and it is carried out in two stages.
[0016] Optionally, the polymerizable monomer is selected from at least one of hydroxyethyl methacrylate, lauryl methacrylate, and polyethylene glycol diacrylate, and the photoinitiator is selected from at least one of Irgacure 651 and Irgacure 184.
[0017] Secondly, this application provides a method for preparing a low-on-state haze liquid crystal dimming film, comprising the following steps:
[0018] The main liquid crystal, the first modified liquid crystal, the second modified liquid crystal, the polymerizable monomer, and the photoinitiator are mixed evenly in proportion to obtain a prepolymer solution.
[0019] The prepolymer liquid is injected into the gap between the substrates with the ITO conductive layer.
[0020] Under the action of an alternating electric field, ultraviolet light is used for two-stage curing, which induces phase separation to form a structure in which liquid crystal microdroplets are dispersed in a polymer matrix.
[0021] Optionally, the two-stage curing process specifically involves: the first stage using light intensity of 5~8 mW / cm². 2Irradiation for 30-60 seconds, followed by a second stage using a light intensity of 10-15 mW / cm². 2 Irradiate for 30-60 seconds.
[0022] Optionally, the frequency of the alternating electric field is 100-500Hz, and the voltage is 50-100V.
[0023] Optionally, the substrate material of the substrate is selected from PC film, PC board, PET film, PET board or glass board.
[0024] The low-open-state haze liquid crystal dimming film provided in the first aspect of this application achieves excellent optical performance by introducing a ternary composite system of host liquid crystal, first modified liquid crystal, and second modified liquid crystal into the liquid crystal phase, particularly the second modified liquid crystal prepared by surface modification of liquid crystal molecules with molybdenum disulfide. Under the action of an electric field, liquid crystal molecules need to be orderly aligned along the direction of the electric field to achieve open-state transparency. Open-state haze mainly originates from interfacial defects between liquid crystal droplets and the polymer matrix, incomplete orientation of liquid crystal molecules, and light scattering caused by uneven distribution of droplet size. By introducing two modified liquid crystals, especially the second modified liquid crystal modified with molybdenum disulfide, this application significantly improves the mobility of liquid crystal molecules in low-temperature environments, enabling the dimming film to maintain a low level of open-state haze even at -30°C.
[0025] The method for preparing a low-open-state haze liquid crystal dimming film provided in the second aspect of this application involves synergistically combining a host liquid crystal with two modified liquid crystal polymerizable monomers and a photoinitiator to form a prepolymer liquid. An alternating electric field is applied in the gap between ITO substrates, combined with two-stage ultraviolet curing, to induce the formation of a liquid crystal microdroplet / polymer composite structure with uniform size and distribution. This not only effectively reduces interface scattering and significantly reduces open-state haze, but also improves the consistency of electric field response and optical stability, achieving high transparency, low haze, and fast response dimming performance. Attached Figure Description
[0026] Figure 1 The photoelectric response curve of the liquid crystal dimming film provided in Embodiment 1 of this application at 25°C. Detailed Implementation
[0027] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit this application.
[0028] The first aspect of this application provides a low-open-state haze liquid crystal dimming film, comprising a liquid crystal phase and a polymer phase, wherein the liquid crystal phase includes a host liquid crystal, a first modified liquid crystal, and a second modified liquid crystal, the second modified liquid crystal being obtained by surface modification of liquid crystal molecules with molybdenum disulfide.
[0029] The low-open-state haze liquid crystal dimming film provided in the first aspect of this application achieves excellent optical performance by introducing a ternary composite system of host liquid crystal, first modified liquid crystal, and second modified liquid crystal into the liquid crystal phase, particularly the second modified liquid crystal prepared by surface modification of liquid crystal molecules with molybdenum disulfide. Under the action of an electric field, liquid crystal molecules need to be orderly aligned along the direction of the electric field to achieve open-state transparency. Open-state haze mainly originates from interfacial defects between liquid crystal droplets and the polymer matrix, incomplete orientation of liquid crystal molecules, and light scattering caused by uneven distribution of droplet size. By introducing two modified liquid crystals, especially the second modified liquid crystal modified with molybdenum disulfide, this application significantly improves the mobility of liquid crystal molecules in low-temperature environments, enabling the dimming film to maintain a low level of open-state haze even at -30°C.
[0030] In some possible implementations, the weight ratio of the liquid crystal phase to the polymer phase is (70~80):(20~30), and the weight ratio of the host liquid crystal, the first modified liquid crystal, and the second modified liquid crystal is (65~75):(8~15):(3~8). For example, the weight ratio of the liquid crystal phase to the polymer phase can be any typical but non-limiting point value or any value between any two points, such as 70:30, 80:30, 70:20, or 80:20; the weight ratio of the host liquid crystal, the first modified liquid crystal, and the second modified liquid crystal can be 65:8:3, 65:15:3, 75:8:3, or 75:15:8. In this case, while ensuring mechanical strength, the driving voltage is reduced. The second modified liquid crystal effectively improves interface compatibility and liquid crystal orientation consistency, and works synergistically with the first modified liquid crystal to regulate the phase separation structure, resulting in more uniform liquid crystal droplet size, fewer interface defects, and a significant reduction in open-state haze.
[0031] Among some possible implementations, the methods for preparing the second modified liquid crystal include:
[0032] Molybdenum disulfide powder was added to hydrochloric acid solution and stirred at 50-80℃ for 1-4 hours for acid activation treatment. Then, it was centrifuged and washed to obtain activated molybdenum disulfide nanoparticles.
[0033] Activated molybdenum disulfide nanoparticles are dispersed in an organic solvent to form a dispersion.
[0034] Liquid crystal monomers and free radical initiators were added to the dispersion, and the mixture was reacted at 65–75 °C for 4–8 hours under inert gas protection to obtain a reaction mixture. The reaction mixture contained, by weight of total solid components, 10–30 wt% activated molybdenum disulfide nanoparticles, 68–88 wt% liquid crystal monomers, and 0.5–3 wt% free radical initiators.
[0035] The reaction mixture was centrifuged, washed, and vacuum dried at 50-70°C for 8-16 hours to obtain the second modified liquid crystal.
[0036] The above-mentioned method for preparing the second modified liquid crystal enhances the surface activity of molybdenum disulfide through acid activation, enabling it to disperse well in the organic phase. Then, liquid crystal monomers are covalently grafted onto the surface of nanoparticles through in-situ free radical polymerization to form a second modified liquid crystal with a core-shell structure. The resulting product combines the orderliness of liquid crystals with the interfacial control capability of molybdenum disulfide. In the dimming film, it can effectively guide the orientation of liquid crystal molecules and reduce scattering centers, thereby significantly reducing open-state haze and improving wide-temperature stability.
[0037] In some possible implementations, the liquid crystal monomer is selected from at least one of 4-cyano-4'-pentylbiphenyl, 4-cyano-4'-heptylbiphenyl, and 4-methoxy-4'-cyanobiphenyl. These liquid crystal monomers not only have excellent compatibility with the host liquid crystal, but can also be effectively grafted onto the surface of activated molybdenum disulfide during polymerization to form a structurally stable second modified liquid crystal.
[0038] In some possible implementations, the average particle size of the molybdenum disulfide nanoparticles is 50-200 nm. Exemplarily, the average particle size of the molybdenum disulfide nanoparticles can be any typical but non-limiting value, such as 50 nm, 100 nm, 150 nm, or 200 nm, or any value between any two points. In this case, it ensures good dispersion in the liquid crystal phase, avoiding increased light scattering due to agglomeration, while also providing sufficient specific surface area for effective grafting of liquid crystal monomers.
[0039] In some possible implementations, the mass-to-volume ratio of molybdenum disulfide powder to hydrochloric acid solution is 1.0 g : 15~25 mL, and the concentration of the hydrochloric acid solution is 0.8~1.2 mol / L. Exemplarily, the mass-to-volume ratio of molybdenum disulfide powder to hydrochloric acid solution can be any typical but non-limiting value such as 1.0 g : 15 mL, 20 mL, 25 mL, or any value between any two such values; the concentration of the hydrochloric acid solution can be any typical but non-limiting value such as 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, or any value between any two such values. In this case, surface impurities can be effectively removed, edge active sites can be increased, and excessive etching that could damage the lamellar structure can be avoided, ensuring efficient grafting of liquid crystal monomers onto the nanoparticle surface.
[0040] In some possible implementations, the free radical initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and benzoyl peroxide. These free radical initiators can efficiently initiate the polymerization of liquid crystal monomers under an inert atmosphere and promote their grafting onto the surface of activated molybdenum disulfide nanoparticles.
[0041] In some possible implementations, the polymer phase is formed by UV-induced phase separation and curing of polymerizable monomers and photoinitiators, with UV curing conditions of 5–15 mW / cm². 2 The irradiation time is 30-120 seconds, divided into two stages. For example, the light intensity can be 5 mW / cm². 2 10mW / cm 2 15mW / cm 2 Typical but non-limiting point values or values between any two points can be used; the irradiation time can be any typical but non-limiting point value or value between any two points, such as 30 seconds, 50 seconds, 80 seconds, 100 seconds, or 120 seconds. In this case, the morphology and pore size distribution of the polymer network are effectively controlled, the orientation consistency of liquid crystal molecules under the electric field is improved, the open-state haze is reduced, and the response speed and optical stability of the dimming film are enhanced over a wide temperature range.
[0042] In some possible implementations, the polymerizable monomers are selected from at least one of hydroxyethyl methacrylate, lauryl methacrylate, and polyethylene glycol diacrylate. These polymerizable monomers form a uniform and stable polymer network during UV-induced phase separation, and their combination takes into account the synergistic regulation of polarity, flexibility, and crosslinking density.
[0043] In some possible implementations, the photoinitiator is selected from at least one of Irgacure 651 and Irgacure 184. These photoinitiators are all α-cleavage type free radical photoinitiators, which can efficiently generate active free radicals under 365 nm ultraviolet light irradiation, and rapidly initiate the polymerization reaction of polymerizable monomers.
[0044] A second aspect of this application provides a method for preparing a low-on-state haze liquid crystal dimming film, comprising the following steps:
[0045] The main liquid crystal, the first modified liquid crystal, the second modified liquid crystal, the polymerizable monomer, and the photoinitiator are mixed evenly in proportion to obtain a prepolymer solution.
[0046] The prepolymer liquid is injected into the gap between the substrates with the ITO conductive layer;
[0047] Under the action of an alternating electric field, ultraviolet light is used for two-stage curing, which induces phase separation to form a structure in which liquid crystal microdroplets are dispersed in a polymer matrix.
[0048] The method for preparing a low-open-state haze liquid crystal dimming film provided in the second aspect of this application involves synergistically combining a host liquid crystal with two modified liquid crystal polymerizable monomers and a photoinitiator to form a prepolymer liquid. An alternating electric field is applied in the gap between ITO substrates, combined with two-stage ultraviolet curing, to induce the formation of a liquid crystal microdroplet / polymer composite structure with uniform size and distribution. This not only effectively reduces interface scattering and significantly reduces open-state haze, but also improves the consistency of electric field response and optical stability, achieving high transparency, low haze, and fast response dimming performance.
[0049] In some possible implementations, the two-stage curing process specifically involves: the first stage using light intensity of 5~8 mW / cm². 2 Irradiate for 30-60 seconds, then in the second stage use a light intensity of 10-15 mW / cm². 2 Irradiate for 30-60 seconds. For example, the first stage uses a light intensity of 5 mW / cm². 2 6mW / cm 2 7mW / cm 2 8mW / cm 2 Typical but non-limiting point values or values between any two points can be used; the irradiation time can be any typical but non-limiting point value or value between any two points, such as 30 seconds, 40 seconds, 50 seconds, or 60 seconds; in this case, it promotes the slow polymerization of polymerizable monomers, induces initial phase separation, and forms uniform polymer nucleation sites. The second stage uses a light intensity of 10 mW / cm². 2 11mW / cm 2 12mW / cm 2 13mW / cm 2 14mW / cm 2 15mW / cm 2 Typical but non-limiting point values or values between any two points can be used, and the irradiation time can be any typical but non-limiting point value or value between any two points, such as 30 seconds, 40 seconds, 50 seconds, or 60 seconds. In this case, the monomer crosslinking is accelerated under the action of an alternating electric field, stabilizing the dispersion structure of liquid crystal microdroplets in the polymer matrix. Through the above two-stage curing process, phase separation kinetics are effectively controlled, resulting in liquid crystal microregions with uniform size and clear interfaces. This can reduce the open-state haze of the dimming film while improving the response speed and optical uniformity.
[0050] In some possible implementations, the frequency of the alternating current electric field is 100-500Hz, and the voltage is 50-100V. For example, the frequency of the alternating current electric field can be any typical but non-limiting value, such as 100Hz, 200Hz, 300Hz, 400Hz, or 500Hz, or any value between any two points; the voltage can be any typical but non-limiting value, such as 50V, 60V, 70V, 80V, 90V, or 100V, or any value between any two points. In this case, the liquid crystal molecules are effectively guided to align orderly along the direction of the electric field, suppressing the disordered aggregation of liquid crystal droplets during the polymerization process.
[0051] In some possible implementations, the substrate material is selected from PC film, PC board, PET film, PET board, or glass board. These substrate materials all have good optical transparency and mechanical stability, and are compatible with the ITO conductive layer; among them, flexible substrates (such as PC and PET films) are suitable for lightweight and flexible dimming devices, while glass boards are suitable for high flatness and high weather resistance scenarios.
[0052] To enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant improvement in the performance of the low-open-state haze liquid crystal dimming film and its preparation method in the embodiments of this application, the above technical solutions are illustrated below through multiple embodiments.
[0053] Preparation of the second modified liquid crystal A:
[0054] 1.0 g of molybdenum disulfide powder was added to 20 mL of 1 mol / L hydrochloric acid solution and stirred at 60 °C for 2 hours for acid activation treatment. After centrifugation, the nanoparticles were washed twice with deionized water and then twice with anhydrous ethanol. The activated molybdenum disulfide nanoparticles were dispersed in 15 mL of anhydrous ethanol. Then, 2.5 g of 4-cyano-4'-pentylbiphenyl monomer and 0.1 g of azobisisobutyronitrile (AIBN) were added, and the mixture was reacted at 70 °C for 6 hours under nitrogen protection. After the reaction was completed, the product was centrifuged, washed three times with ethanol, and dried under vacuum at 60 °C for 12 hours to obtain the second modified liquid crystal A.
[0055] Preparation of the second modified liquid crystal B:
[0056] Following the preparation method of the second modified liquid crystal A, the 4-cyano-4'-pentylbiphenyl monomer was replaced with the 4-cyano-4'-heptylbiphenyl monomer, while other conditions remained unchanged, to obtain the second modified liquid crystal B.
[0057] Preparation of the second modified liquid crystal C:
[0058] Following the preparation method of the second modified liquid crystal A, the amount of molybdenum disulfide powder was adjusted to 1.5g, while other conditions remained unchanged, to obtain the second modified liquid crystal C.
[0059] Example 1
[0060] A prepolymer solution was prepared by uniformly mixing 70 parts by weight of SLC-1717 (Shijiazhuang Chengzhi Yonghua Display Materials Co., Ltd.) as the main liquid crystal, 10 parts by weight of RM257 (first modified liquid crystal, Merck GmbH, Germany), 5 parts by weight of second modified liquid crystal A, 15 parts by weight of hydroxyethyl methacrylate (HEA), 10 parts by weight of polyethylene glycol diacrylate (PEGDA600), and 1.5 parts by weight of Irgacure 651 photoinitiator. The prepolymer solution was then injected into a PC substrate with an ITO conductive layer (gap thickness of 15 μm). Under an AC electric field of 100 Hz and 80 V, the prepolymer solution was first applied at 6 mW / cm². 2 Irradiate with ultraviolet light for 45 seconds, then use 12mW / cm 2 Irradiate with ultraviolet light for 45 seconds to complete curing and obtain a liquid crystal dimming film.
[0061] Example 2
[0062] Following the method of Example 1, the second modified liquid crystal A was replaced with the second modified liquid crystal B, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0063] Example 3
[0064] Following the method of Example 1, the second modified liquid crystal A was replaced with the second modified liquid crystal C, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0065] Example 4
[0066] Following the method of Example 1, the ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal A was adjusted to 80:15:5, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0067] Example 5
[0068] Following the method of Example 1, the ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal A was adjusted to 70:20:5, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0069] Example 6
[0070] Following the method in Example 1, the UV curing conditions were adjusted as follows: 8 mW / cm² in the first stage. 2 Irradiation for 60 seconds, followed by a second stage of irradiation at 15mW / cm² for 60 seconds, with other conditions remaining unchanged, yields a liquid crystal dimming film.
[0071] Example 7
[0072] Following the method in Example 1, the UV curing conditions were adjusted as follows: 5mW / cm² in the first stage. 2Irradiation for 30 seconds, second stage 10mW / cm 2 Irradiate for 30 seconds, keeping other conditions unchanged, to obtain a liquid crystal dimming film.
[0073] Comparative Example 1
[0074] Following the method of Example 1, without adding the second modified liquid crystal, the ratio of the main liquid crystal to the first modified liquid crystal is adjusted to 80:15, and other conditions remain unchanged, to obtain a liquid crystal dimming film.
[0075] Comparative Example 2
[0076] Following the method of Example 1, the second modified liquid crystal A was replaced with 4-cyano-4'-pentylbiphenyl monomer (5 parts by weight), while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0077] Comparative Example 3
[0078] Following the method of Example 1, the ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal A was adjusted to 85:10:5, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0079] Comparative Example 4
[0080] Following the method of Example 1, the ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal A was adjusted to 65:25:5, while other conditions remained unchanged, to obtain a liquid crystal dimming film.
[0081] Comparative Example 5
[0082] Following the method in Example 1, single-stage UV curing was employed: 10 mW / cm². 2 Irradiate for 90 seconds, keeping other conditions unchanged, to obtain a liquid crystal dimming film.
[0083] The performance of the liquid crystal dimming films prepared in the above embodiments and comparative examples was tested.
[0084] The testing standards or methods are as follows:
[0085] Haze and transmittance were measured according to ASTM D1003 standards using a haze meter / transmittance meter. Samples were measured in both the "on" (voltage applied) and "off" (no voltage applied) states, and in environmental chambers at -35°C and 25°C to ensure temperature control. The threshold voltage was applied at 100Hz AC, with the voltage amplitude gradually increased while the transmittance of the sample was monitored in real time.
[0086] The results are shown in Table 1 below.
[0087] Table 1
[0088] Example 1 6.2 87.5 3.6 96.8 13.2 Example 2 6.8 86.9 3.3 96.5 13.5 Example 3 5.9 88.1 2.8 97.2 12.8 Example 4 7.1 85.3 4.3 95.9 14.1 Example 5 6.5 86.7 3.7 96.3 13.8 Example 6 5.5 89.2 2.5 97.8 12.5 Example 7 7.8 84.1 4.3 95.2 14.8 Comparative Example 1 15.6 82.3 10.6 93.5 18.7 Comparative Example 2 18.2 78.6 13.2 90.1 22.3 Comparative Example 3 9.8 83.7 6.9 94.2 16.5 Comparative Example 4 8.5 84.9 4.8 94.8 15.9 Comparative Example 5 12.3 83.1 7.6 94.5 17.2
[0089] As shown in Table 1, this invention successfully prepared a liquid crystal dimming film with excellent wide-temperature performance by introducing two modified liquid crystals (especially the second modified liquid crystal based on molybdenum disulfide modification) and optimizing the ultraviolet light-induced phase separation process. Specifically, the liquid crystal dimming films of Examples 1-7 exhibited open-state haze ≤8% at -30℃ and open-state haze ≤4.5% at 25℃, significantly better than Comparative Examples 1-5, demonstrating that the introduction of the second modified liquid crystal significantly improved low-temperature performance. The threshold voltage of Examples 1-7 was ≤15V, significantly lower than that of Comparative Examples 1-5, indicating that this invention effectively reduced the driving voltage. Example 6 employed specific ultraviolet curing conditions (8mW / cm²). 2 +15mW / cm 2 This improved phase separation and further reduced open-state haze. Comparative Example 1 did not contain the second modified liquid crystal, and Comparative Example 2 used unmodified liquid crystal monomers, resulting in a significant increase in open-state haze at low temperatures. The liquid crystal ratios of Comparative Examples 3 and 4 exceeded a specific range, and their performance was significantly inferior to that of the examples.
[0090] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of protection of this application is limited to these examples; within the framework of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of one or more embodiments of this application as described above, which are not provided in detail for the sake of brevity.
[0091] One or more embodiments in this application are intended to cover all such substitutions, modifications, and variations that fall within the broad scope of this application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of one or more embodiments in this application should be included within the protection scope of this application.
Claims
1. A low-on-state haze liquid crystal dimming film, characterized in that, It includes a liquid crystal phase and a polymer phase, wherein the liquid crystal phase includes a bulk liquid crystal, a first modified liquid crystal, and a second modified liquid crystal, wherein the second modified liquid crystal is obtained by surface modification of liquid crystal molecules with molybdenum disulfide.
2. The low-on-state haze liquid crystal dimming film according to claim 1, characterized in that, The weight ratio of the liquid crystal phase to the polymer phase is (70~80):(20~30), and the weight ratio of the main liquid crystal, the first modified liquid crystal, and the second modified liquid crystal is (65~75):(8~15):(3~8).
3. The low-on-state haze liquid crystal dimming film according to claim 1 or 2, characterized in that, The preparation method of the second modified liquid crystal includes: Molybdenum disulfide powder was added to hydrochloric acid solution and stirred at 50-80℃ for 1-4 hours for acid activation treatment. Then, it was centrifuged and washed to obtain activated molybdenum disulfide nanoparticles. The activated molybdenum disulfide nanoparticles are dispersed in an organic solvent to form a dispersion. A liquid crystal monomer and a free radical initiator are added to the dispersion, and the mixture is reacted at 65-75°C for 4-8 hours under inert gas protection to obtain a reaction mixture; wherein, based on the total mass of solid components in the reaction mixture, the activated molybdenum disulfide nanoparticles account for 10-30 wt%, the liquid crystal monomer accounts for 68-88 wt%, and the free radical initiator accounts for 0.5-3 wt%. The reaction mixture was centrifuged, washed, and vacuum dried at 50-70°C for 8-16 hours to obtain the second modified liquid crystal.
4. The low-on-state haze liquid crystal dimming film according to claim 3, characterized in that, The liquid crystal monomer is selected from at least one of 4-cyano-4'-pentylbiphenyl, 4-cyano-4'-heptylbiphenyl, and 4-methoxy-4'-cyanobiphenyl; And / or, the average particle size of the molybdenum disulfide nanopowder is 50~200 nm; And / or, the mass-to-volume ratio of the molybdenum disulfide powder to the hydrochloric acid solution is 1.0 g : 15~25 mL, and the concentration of the hydrochloric acid solution is 0.8~1.2 mol / L.
5. The low-on-state haze liquid crystal dimming film according to any one of claims 1 to 4, characterized in that, The polymer phase is formed by UV-induced phase separation and curing of polymerizable monomers and photoinitiators. The UV curing conditions are: light intensity 5~15mW / cm². 2 The irradiation time is 30-120 seconds, and it is carried out in two stages. And / or, the main liquid crystal is selected from Shijiazhuang Chengzhi Yonghua Display Materials Co., Ltd. SLC-1717; And / or, the first modified liquid crystal is selected from Merck RM257.
6. The low-on-state haze liquid crystal dimming film according to claim 5, characterized in that, The polymerizable monomer is selected from at least one of hydroxyethyl methacrylate, lauryl methacrylate, and polyethylene glycol diacrylate, and the photoinitiator is selected from at least one of Irgacure 651 and Irgacure 184.
7. A method for preparing a low-on-state haze liquid crystal dimming film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: The main liquid crystal, the first modified liquid crystal, the second modified liquid crystal, the polymerizable monomer, and the photoinitiator are mixed evenly in proportion to obtain a prepolymer solution. The prepolymer liquid is injected into the gap between the substrates with the ITO conductive layer. Under the action of an alternating electric field, ultraviolet light is used for two-stage curing, which induces phase separation to form a structure in which liquid crystal microdroplets are dispersed in a polymer matrix.
8. The method for preparing a low-on-state haze liquid crystal dimming film according to claim 7, characterized in that, The two-stage curing process specifically involves: the first stage using light intensity of 5~8mW / cm². 2 Irradiation for 30-60 seconds, followed by a second stage using a light intensity of 10-15 mW / cm². 2 Irradiate for 30-60 seconds.
9. The method for preparing a low-on-state haze liquid crystal dimming film according to claim 7 or 8, characterized in that, The frequency of the alternating electric field is 100-500Hz, and the voltage is 50-100V.
10. The method for preparing a low-on-state haze liquid crystal dimming film according to claim 9, characterized in that, The substrate material is selected from PC film, PC board, PET film, PET board or glass board.
